Comparative Evaluation of the Different Assessment Methods of Life Quality in Patients with Vitreoretinal Pathology - I. G. Ovechkin; A. V. Malyshev; G. Yu. Karapetov; T. A. Avanesova; N. I. Ovechkin; V. E. Yudin (Oftalʹmologiâ)
Effectiveness of the patients with the vitreoretinal pathology with different quality of life (QL) comparative evaluation methods. Methods. 129 patients (before and after standard vitrectomy) with the 3 types of the vitreretinal pathology were examined (38 — with intraocular hemorrhage, 43 — proliferative diabetic retinopathy (PDR), 48 — retinal detachment). Complex examination (36 clinical, haemodynamic and electrophysiological indications) were performed before and 1 month after surgery. QL research was based on the QL-25 (Russian type of the VFQ-25), QL-9 (Russian type of VF-14) and authorial QL-20 questionnaire. Results. QL increasing was detected after the surgery (15.8–20.9%) in all cases of the vitreoretinal pathology type. Correlation analysis of the different QL hasshown obvious QL-20 advantages, comparing to QL-9 and mostly QL-25, that was indicated by the statistically significant difference of the middle (all 36 indicators) KK (0,44±0,02; 0,35±0,02; 0,15±0,03) and higher KK relating to prognostic informative vision indicators (0,75–0,84; 0,69–0,74; 0,21–0,70). Conclusion. Results indicate actuality of the QL-20 method adaption in dispensary observation of the patients with different types of vitreoretinal pathology.